La correspondencia postal entre Josemaría Escrivá de Balaguer y Ernestina de Champourcin (1959-1974) / The postal correspondence between Josemaría Escrivá and Ernestina de Champourcin (1959-1974) - Antonio Rodríguez Tovar (Studia et Documenta, 2025)
The postal correspondence between Josemaría Escrivá and Ernestina de Champourcin (1959-1974) Edition and commentary on the exchange of letters and postcards among the founder of Opus Dei and Ernestina de Champourcin, from 1959 until 1974.